Generating receptive endometrium in Asherman's syndrome - Gargett, Caroline E (Medknow Publications Pvt Ltd, 2011)
Intrauterine administration of bone marrow stem/progenitor cells to a woman with thin endometrium refractory to estrogen stimulation regenerated her endometrium sufficiently to support a pregnancy. Or was it local endometrial damage induced by concurrent curettage that stimulated endogenous endometrial stem/progenitor cells into action? Or both?